2011
DOI: 10.1002/vnl.20250
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated poly(vinyl chloride) stabilization by pentaerythritol/calcium‐zinc stearate mixtures: The fate of pentaerythritol

Abstract: The stabilization effect of pentaerythritol (Pe) combined with calcium and zinc stearates (CaSt2/ZnSt2) on chlorinated poly(vinyl chloride) (CPVC) is investigated. Congo red and dynamic thermal stability data indicate that Pe alone has a mild stabilizing effect on the degradation of CPVC. Addition of mixed CaSt2/ZnSt2 to this system leads to a significant improvement in stability. Thermogravimetric studies indicate that premature weight loss, not observed with either Pe alone or with CaSt2/ZnSt2, is observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…It has been reported that, in the case of stearate, the efficacy of mixed Ca/Zn stabilizers can be enhanced by using a co-stabilizer ( El-Ghaffar et al., 2019 ; Gao et al., 2012 ; Ikeda et al., 2003 ). It is known also that pentaerythritol is a good co-stabilizer and has synergistic effects with mixed Ca/Zn stearates ( Liao et al., 2011 ; Liu et al., 2007 ; Schiller, 2015 ). To check whether the same synergy exhibited between mixed Ca/Zn-Palmate and pentaerythritol, two samples with mixed Ca/Zn-Palmate/pentaerythritol have been evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that, in the case of stearate, the efficacy of mixed Ca/Zn stabilizers can be enhanced by using a co-stabilizer ( El-Ghaffar et al., 2019 ; Gao et al., 2012 ; Ikeda et al., 2003 ). It is known also that pentaerythritol is a good co-stabilizer and has synergistic effects with mixed Ca/Zn stearates ( Liao et al., 2011 ; Liu et al., 2007 ; Schiller, 2015 ). To check whether the same synergy exhibited between mixed Ca/Zn-Palmate and pentaerythritol, two samples with mixed Ca/Zn-Palmate/pentaerythritol have been evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…This is evidence that the hydrogen chloride scavenging by pentaerythritol works well and may even be faster than that by Ca-Palmate. This is understandable because the reactivity of pentaerythritol is increased in the presence of ZnCl 2 and CaCl 2 (Liao et al, 2011), which are produced through the stabilization of PVC by the mixed Ca/Zn-Palmate system. As can be seen from Figure 4, with the addition of pentaerythritol into the formula, even though it has been heated for 50 minutes, the presence of Ca/Zn-Palmate can J o u r n a l P r e -p r o o f still be observed.…”
Section: Stabilization Mechanismmentioning
confidence: 99%
“…Generally, chlorinated polymers, such as, chlorinated polyethylene, chlorinated PVC and chlorinated rubber (Kar et al , 2010; Liao et al , 2015; Moulay, 2010), is a kind of materials with poor heat resistance performance. To investigate the heat resistance of RR after chlorination, their TG and TGA testing are conducted, and the curves are recorded in Figure 4.…”
Section: Performancesmentioning
confidence: 99%
“…Due to the higher chlorine content of CPVC than PVC, it has good comprehensive performance including heat resistance, flame retardant, low thermal conductivity, which makes it widely used in electrical products accessories, packaging materials, construction materials, transportation facilities fields and so on 3–6 . However, CPVC has poor thermal stability without the addition of stabilizers and lubricants 7 . Hence, CPVC is still a fire hazard when it is used as materials such as pipes and plates.…”
Section: Introductionmentioning
confidence: 99%